The Reality of Gender Mainstreaming in Madaba Governorate Municipalities - El Kharouf, Amal; Al Dahamesheh, Jumman; Abul Rous, Rula (Dirasat: Human and Social Sciences, 2024)
Objectives: The aim of this study is to assess the state of gender mainstreaming in the four municipalities of the Madaba Governorate (n = 4). Methods: To achieve the study’s objectives, both survey and qualitative approaches were pursued. An interview-based survey method was used to gather quantitative data from a representative sample of the study community, comprising all the employees in the municipalities of the Madaba Governorate. Of these, 38.8% were women and 62.09% were men. Data was collected through a questionnaire. To enhance the study’s results, a qualitative approach was also employed, wherein interviews were conducted with 20 individuals in various leadership positions across the Madaba communities. Results: The results indicated a gender gap in terms of accessibility to leadership positions, with women having less access and being underrepresented in certain committees. Women also did not receive equal opportunities in training courses and conferences outside Jordan. The study also revealed a moderation in attitudes toward general women’s participation in development. However, these attitudes varied based on job position and gender awareness. Men tended to have more negative attitudes toward women’s participation in development. The results also noted modest women’s participation in identifying needs, planning, implementing, monitoring, and evaluating locally implemented programs. Conclusion: The study concludes that the programs of Madaba’s municipalities are somewhat responsive to the needs and roles of women.